Mutations in AXIN2 Cause Familial Tooth Agenesis and Predispose to Colorectal Cancer - Lammi, Laura; Arte, Sirpa; Somer, Mirja; Järvinen, Heikki; Lahermo, Päivi; Thesleff, Irma; Pirinen, Sinikka; Nieminen, Pekka (American journal of human genetics, 2004)
Wnt signaling regulates embryonic pattern formation and morphogenesis of most organs. Aberrations of regulation of Wnt signaling may lead to cancer. Here, we have used positional cloning to identify the causative mutation in a Finnish family in which severe permanent tooth agenesis (oligodontia) and colorectal neoplasia segregate with dominant inheritance. Eleven members of the family lacked at least eight permanent teeth, two of whom developed only three permanent teeth. Colorectal cancer or precancerous lesions of variable types were found in eight of the patients with oligodontia. We show that oligodontia and predisposition to cancer are caused by a nonsense mutation, Arg656Stop, in the Wnt-signaling regulator AXIN2. In addition, we identified a de novo frameshift mutation 1994-1995insG in AXIN2 in an unrelated young patient with severe tooth agenesis. Both mutations are expected to activate Wnt signaling. The results provide the first evidence of the importance of Wnt signaling for the development of dentition in humans and suggest that an intricate control of Wnt-signal activity is necessary for normal tooth development, since both inhibition and stimulation of Wnt signaling may lead to tooth agenesis. Our findings introduce a new gene for hereditary colorectal cancer and suggest that tooth agenesis may be an indicator of cancer susceptibility.